ASPEK-ASPEK YANG MEMPENGARUHI AKHLAK SERTA AKTUALISASI DALAM KEHIDUPAN SEHARI-HARI - Nada, Fadya Shofa; Maulani, Dinda Fadhilah; Widiyanto, Firman Hadi; Syam, Ilyas; Fhajri, Jihan; Fauziyah, Hana; Sitika, Achmad Junaedi (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The importance of understanding these human factors becomes especially clear when we consider the role of humans as moral agents. Human activities are greatly influenced by the environment and surrounding conditions. Therefore, we must study the most important factors that shape and influence human behavior as well as its actualization in everyday life, such as morals towards Allah, morals towards fellow humans and morals towards the environment. The five factors discussed in this text are habits or customs, instincts or instincts, environment, education and media.